A Telecommunication System Based on Wireless Relay Network - Shakya, Dishan; Dahal, Diwas; Shrestha, Nabin; Maharjan, Sajen; Acharya, Praches (KEC Journal of Science and Engineering, 2026)
A wireless relay network is made up of multiple low-power nodes that pass messages between two endpoints by forwarding them through intermediate helper nodes. This relay process greatly increases the communication range of small wireless devices but requires a custom communication protocol rather than traditional centralized routing methods. In this work, we present the FMTG (Find Me That Guy) protocol, a multi-hop system that uses simple broadcast discovery and chained acknowledgements to build communication paths. It removes the need for periodic control messages entirely, cutting idle overhead by 100% compared to protocols like OLSR and BATMAN and uses a compact 28-byte packet with an 11-byte header to keep communication efficient. Practical experiments with microcontroller-based nodes show that this approach extends communication distance from about 15 m to 38 m across four hops. These results demonstrate that it is a low-overhead and power-efficient option for building distributed communication networks.